Sistem Ekonomi Bani Umayyah: Perkembangan dan Pengaruhnya terhadap Perekonomian Islam: The Umayyad Economic System: Its Development and Influence on the Islamic Economy - Indah, Mahira; Gaffar, Andi Abdul; Siradjuddin, Siradjuddin (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The Umayyad Dynasty was the first Islamic empire, and independence in various aspects, including economic self-sufficiency, was essential to achieve the welfare of society and ensure the dynasty’s continuity. Throughout its long period of rule, the Umayyad Dynasty was led by 14 caliphs, each with their unique leadership style. However, only three of these caliphs succeeded in bringing the Umayyad Dynasty to its peak: Mu'awiyah bin Abi Sufyan, Abdul Malik bin Marwan, and Umar bin Abdul Aziz. Economic growth increased during the reign of the Umayyads compared to previous periods. The economic improvements that brought prosperity to the people of this dynasty were a direct result of the caliphs’ policies, supported by public participation. This study aims to understand the economic concepts implemented by Muslims during the Umayyad era. Using a library research method with a descriptive-analytical and qualitative approach, the study reviews the concept of “property law” through related articles. The analysis shows that during the Umayyad period, the economy grew more rapidly than in previous times, with prosperity resulting from the policies of the caliphs, particularly Mu'awiyah bin Abi Sufyan, Abdul Malik bin Marwan, and Umar bin Abdul Aziz. Their policies, along with the support of the public, played a crucial role in the economic growth of the Umayyad era. Changes in Islamic life occurred swiftly, encompassing various fields of knowledge such as religion, architecture, science, technology, and economics.